Discourse Analysis: Kinship Politics in the 2020 Regional Head Election - Moch Edward Trias Pahlevi; Azka Abdi Amrurobbi; Muhammad Iqbal Khatami; Bambang Eka Cahya Widodo (Ministry of Home Affairs, 2021)
After the issuance of the Constitutional Court Decision No.33 / PUU-Xlll / 2015 as the cancellation of the ban on dynastic politics, a number of candidates from the incumbent's relatives advanced in the direct Pilkada and mushroomed up to the 2020 regional elections. The occurrence of kinship politics is not only seen in terms of regulation, but the rise of kinship politics is also due to problems in political parties in carrying out the political recruitment function. This study seeks to analyze the findings of the online media reported in Kompas and Tempo. This study uses qualitative methods and uses Nvivo 12 Plus in processing data. In this study, it is explained that the factors for the formation of dynastic politics from online media coverage of Kompas dominantly explains the recruitment of political parties which are less democratic, while Tempo online media dominantly explains that the supporting factors for the formation of kinship politics are party recruitment, family support, and weak legal rules. In addition, the impact of kinship politics from the analysis of Kompas online media reports is the creation of corrupt behaviour and damaging the bureaucratic order. Meanwhile, the impact of kinship politics from the analysis of Tempo online media is the decline in the quality of democracy and damage to the structure of the party. This type of research used in this research is qualitative research. The analysis used in this paper is descriptive analysis. Analysis was performed using the Nvivo 12 plus software.